The historical basis of the «San Martín miracle»: territorial control and state strategies against drug trafficking and subversive organizations (1980-1995) - Manrique López, Hernán (2015)
The present article demonstrates the historical bases previous to the success of alternative development in the region San Martín. It shows that anti-drug policy was unable to successfully function during the 1980s due to an absence of basic security conditions in the region. The ar- ticle’s main objective consists in presenting how the state managed to meet said security condi- tions. Thus, this article is divided into two periods of analysis. First, it focuses on the time period from 1980 to 1989 and shows how generalized state repression resulted counterproductive in the region because of strong subversive forces. Second, it presents the time period from 1989 to 1995 and demonstrates how the exercise of sequential period of focalized repression facilitated an environment to fight against drug trafficking. In this way, the focalized strategy and sequence permitted the state to resume security conditions that in a post-boom and post-conflict situation permitted the implementation of alternative development programs.